The Effect of Two Obstacle Jump Rope Training on the Results of Long Jump Squatting Style of Class VIII Students of SD Negeri 2 Toman - Irawan, Novi; Imansyah, Farizal; Lanos, Muhsana El Cintami (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study was to determine the effect of two-obstacle jump rope training on the results of long jump squatting style of grade VI students of SD Negeri 2 Toman in the 2022/2023 academic year. The variables in the study, namely the exercise of jumping rope two obstacles as the independent variable (X) and the results of long jump squatting style as the dependent variable (Y). The population in this study was 212 male students of grade VI SD Negeri 2 Toman. The samples in this study were taken by 2 classes using cluster random sampling techniques so that class V1a was obtained as an experimental class of 17 students, and V1b as a control class of 17 students. The method used in this study is experimental. Data collection is carried out by means of tests. The data obtained from the tests are analyzed by averaging and using t-test statistics. The results of data analysis showed that the average increase in squatting style long jump ability of experimental group students was better than the control group or 0.12 > 0.05. The results of hypothesis testing are shown by the value of the calculated test coefficient greater than the t-table coefficient or 3.28 > 1.696, then Ho is rejected and Ha is accepted, this means that there is an effect of jumping rope training two obstacles on the results of long jump squatting style of grade VI students of SD Negeri 2 Toman.